An Empirical Assessment of Cases Experienced during Inpatient Family Medicine Resident Training in a Rural Community Hospital of the Shizuoka Family Medicine Training Program in Japan. (30th October 2015) - Tsunawaki, Shinji; Inoue, Machiko; Fetters, Michael D.
Abstract : Background: Despite emerging national interest in training family physicians to improve access to medical services in health care shortage areas, empirical data on inpatient resident learning experiences in rural community settings has been lacking. This research sought to understand the breadth of diagnoses, patient demographics, and comorbidities experienced by family medicine residents while training in a newly launched family medicine training program in a rural area in Shizuoka prefecture. Methods: The design employed secondary dataset analysis from a 260‐bed hospital in rural Shizuoka. Using the hospital administrative database, a dataset was developed of all patient admissions from 9/1/2011 to 8/31/2012 including the Diagnosis Procedure Combination (DPC) code, patient age and gender, and the physician of record. The main outcome measures were frequency and distribution of diagnostic groups and diagnoses in family medicine residents. Secondary outcomes included three or more comorbidities and hospital readmissions. Results: There were 3474 admissions (males/females 1867/1607) and 8 residents who were the physician of record for 220 cases (mean 27.5 cases/resident, range 10–56), about 6.3% of the total hospital admissions during this timeframe. The mean age of resident cases was 71 years of age (range 0–101 years). Distribution by diagnostic groups included: gastrointestinal (61), pulmonary (41), cardiovascular (28), and neurological (25). The most common diagnoses included: pneumonia (34), congestive heart failure (21), stroke (16), intestinal obstruction (15), and urinary tract infection (10). Seventy‐seven percent (170/220) of cases had one or more comorbidities and 36% of cases had three or more comorbidities which were significantly less than hospital as a whole (46% of cases with three or more comorbidities). Conclusions: The community hospital setting provides an excellent training environment for family medicine residents because the setting and the care experienced reflects content of what the training program aspires for the residents to provide in the future. Community hospital training serves policy maker's agenda for developing a systematic primary care training system appropriate for health care shortage area community‐based care.